Combined biological and chemical control of Fusarium associated with Eldana Saccharina walker in South African sugarcane production - Cele, Tholakele Gladness (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Bioinformatics)
Restricted access. Expected release in 2026.
Keywords: Uncatalogued